2014
DOI: 10.3390/md13010048
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Absorption of Fucoidan Extracted from the Brown Seaweed, Cladosiphon okamuranus

Abstract: The aim of this study was to examine the absorption of fucoidan through the intestinal tract. Fucoidan (0.1, 0.5, 1.0, 1.5 and 2.0 mg/mL) was added to Transwell inserts containing Caco-2 cells. The transport of fucoidan across Caco-2 cells increased in a dose-dependent manner up to 1.0 mg/mL. It reached a maximum after 1 h and then rapidly decreased. In another experiment, rats were fed standard chow containing 2% fucoidan for one or two weeks. Immunohistochemical staining revealed that fucoidan accumulated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 36 publications
2
88
0
1
Order By: Relevance
“…The uptake of fucoidan through the intestinal tract seemed to be low, but was measurable by our ELISA method (18). The transport of fucoidan across Caco-2 cells was demonstrated in a dose-dependent manner (21,22) and reached a maximum after 1 h, followed by a rapid decrease. Immunohistochemical staining revealed that fucoidan accumulated in jejunal macrophages and hepatic Kupffer cells in fucoidan-treated rats (22).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The uptake of fucoidan through the intestinal tract seemed to be low, but was measurable by our ELISA method (18). The transport of fucoidan across Caco-2 cells was demonstrated in a dose-dependent manner (21,22) and reached a maximum after 1 h, followed by a rapid decrease. Immunohistochemical staining revealed that fucoidan accumulated in jejunal macrophages and hepatic Kupffer cells in fucoidan-treated rats (22).…”
Section: Discussionmentioning
confidence: 93%
“…The transport of fucoidan across Caco-2 cells was demonstrated in a dose-dependent manner (21,22) and reached a maximum after 1 h, followed by a rapid decrease. Immunohistochemical staining revealed that fucoidan accumulated in jejunal macrophages and hepatic Kupffer cells in fucoidan-treated rats (22). The molecular weight of fucoidan detected in serum was similar to that of the ingested fucoidan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been reported that certain polysaccharides could be transported across the intestinal epithelium. For example, Nagamine et al reported that high molecular weight fucoidan was absorbed through intestinal epithelial cells both in vivo and in vitro (Nagamine et al, 2014). Zuo et al proposed that squid ink polysaccharide could be permeated through the Caco-2 cells monolayer and P app was 1.44 Â 10 À6 cm/s (Zuo et al, 2016).…”
Section: Investigation Of Endocytosis Pathways In Caco-2 Cellsmentioning
confidence: 99%
“…Biodistribution studies for 20 days after injection of anti-epidermal growth factor receptor (anti-EGFR) encapsulated in fucoidan-coated gold nanorods revealed the highest accumulation of gold in liver and spleen followed by heart, lungs, kidney and tumors. Fucoidan can thus be said to exhibit preferential accumulation in liver and low levels in systemic circulation (Atashrazm et al, 2015;Nagamine et al, 2015;Manivasagan et al, 2017). Rapid clearance of ultrasmall superparamagnetic iron oxide nanoparticles coated with 99m Tc labeled fucoidan (USPIO-FUCO) was recorded with half-life of 9 min for rapid component when administered intravenously by a single injection in male Wistar rats.…”
Section: Adme Of Marine Sulfated Polysaccharidesmentioning
confidence: 99%